EFFECT OF WATER-SETTABLE GIC IMMERSION IN RIVER WATER AND PDAM WATER ON DIAMETRAL TENSILE STRENGTH - Raden Harry Dharmawan Setyawardhana; Sherli Diana; Muhammad Rezky Gunawan (Dentino : Jurnal Kedokteran Gigi, 2021)
ABSTRACTBackground: Dental and oral health problems according to Riskesdas (2018) in Indonesia is 57.6% and South Borneo is almost 60%. High level of damage in South Borneo is caused by the people still consumption of river water as a source of clean water. Caries can be treated by restoration of tooth, one of them is water settable GIC.. Objective: Knowing the effect of water settable GIC immersion in river water and PDAM water to diametric tensile strength. Method: This study used a true experimental laboratory research method with a post test only design with a control group design on 27 samples which were divided into 3 groups immersion.  Result: This research shows that the mean of diametric tensile strength in group 1 (7.15 MPa), group 2 (8.42 MPa), and group 3 (10.54 MPa). The One Way Anova statistical test shows the value of (P <0.05) which means that there is a significant difference in the value of the diametric tensile strength of each treatment group. Conclusion: There is an effect on the decrease in the value of the diametric tensile strength after immersion of water settable GIC in river water and PDAM water.Keyword: Diametral Tensile Strength, GIC Immersion, River Water.